2020
DOI: 10.1021/acschemneuro.9b00639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of [18F]-N-Methyl lansoprazole as a Tau PET Imaging Agent in First-in-Human Studies

Abstract: Development of positron emission tomography (PET) imaging agents capable of quantifying tau aggregates in neurodegenerative disorders such as Alzheimer's disease (AD) is of enormous importance in the field of dementia research. The aim of the present study was to conduct first-inman imaging studies with the potential novel tau imaging agent [ 18 F]N-methyl lansoprazole ([ 18 F]NML). Herein we report validation of the synthesis of [ 18 F]NML for clinical use by labeling the trifluoromethyl group via radiofluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…In this case, these agents will never reach their intended subcellular target(s). Such promiscuous or selective substrates would be of great use as AD diagnostics [e.g., positron emission tomography (PET) tracers] to track ABC transporter function at the BBB itself [60] (e.g., ABCB1 [61,62] or ABCC1 [63,64]). However, for future drug design of AD therapeutics to affect ABC transporters participating in (subcellular) vesicle membrane formation and composition, these compounds should rather not be substrates but allosteric modulators.…”
Section: Vesicular Abc Transporters: Implications For Pharmacokineticsmentioning
confidence: 99%
“…In this case, these agents will never reach their intended subcellular target(s). Such promiscuous or selective substrates would be of great use as AD diagnostics [e.g., positron emission tomography (PET) tracers] to track ABC transporter function at the BBB itself [60] (e.g., ABCB1 [61,62] or ABCC1 [63,64]). However, for future drug design of AD therapeutics to affect ABC transporters participating in (subcellular) vesicle membrane formation and composition, these compounds should rather not be substrates but allosteric modulators.…”
Section: Vesicular Abc Transporters: Implications For Pharmacokineticsmentioning
confidence: 99%
“…This (Riss and Aigbirhio 2011). This radiochemistry underwent various improvements (Kramer et al 2020). In 2020, Riss and Scott implemented this protocol for the synthesis [ 18 F]N-methyl lansoprazole ([ 18 F]NML) (4.6% RCY and A m = 120.1 GBq/μmol), a candidate for Alzheimer's Tau imaging (Frost et al 2019).…”
Section: Radiosynthesis Of [ 18 F]trifluoromethyl-containing Moleculesmentioning
confidence: 99%
“…Moreover, the authors found that the ratio of [ 18 F]difluoromethylidene increased, and the radiochemical yield of [ 18 F]LNS was not higher than 7%. Kramer et al described the synthesis of fluorine-18-labelled N-methyl lanosoprazole ([ 18 F]NML), an analogue of lansoprazole (Scheme 4) [45]. They followed the procedure reported by Fawaz et al involving nucleophilic addition of n.c.a.…”
Section: Aliphatic [ 18 F]cf 3 Compoundsmentioning
confidence: 99%